AGE-RELATED DEVELOPMENT OF RUN-UP VELOCITY ON VAULT - Stefan Brehmer; Falk Naundorf (Science of Gymnastics Journal)
The run-up velocity on vault is described in many publications as an important factor to generate the energy for the subsequent motion segments of a vault. For a high run-up velocity both, biological backgrounds and empirical investigation show a steady increase in speed until the start of men’s senior gymnastics age. Different mechanisms are responsible for this circumstance. Thus the increases of the running velocity during childhood and up to pubescence are due to primarily informational or coordinative development. From the beginning of puberty the faster sprint performance, especially in male gender, can be explained by conditional developments based on changed hormones level. To proof the explanations we compared the age related velocity in different stages of motor development, using run-ups of the last four years at various high level competitions. There is an increase in the velocity up to the end of men’s junior gymnastics age, followed by stagnation in senior age. The speed increase in pubescence and adolescence do not differ. Therefore coordinative and conditional factors determined the development of run-up velocity equally.